The attractive effects of amino acids and some classical substances on grass carp (Ctenopharyngodon idellus) - Yu, Haojie; Wang, Xiaoyu; Kong, Fanshuang; Song, Xuedong; Tan, Qingsong (Fish physiology and biochemistry, 2021)
Grass carp ( Ctenopharyngodon idellus ) is one of the most essential fishing species in China. The bait for this fish is rapidly developing. However, the study on the attractants in the bait for this fish lacks. This study was designed to systematically investigate the effects of 16 kinds of test substances on the perspective of behaviour and physiology of grass carp by using different kinds of methods, including behavioral tests (maze test and biting-balls test) and electro-olfactogram (EOG). Our experiment’s idea is mainly to imitate: in addition to vision, fish in nature also use smell to find food and finally swallow under the action of olfaction, taste, and other sensory systems. Firstly, the behavioral maze test was used to screen the attractive or suppressive effect of 16 test substances on grass carp, and the electronic olfactory recording method was used to further evaluate the olfactory response of grass carp to the eight stimuli selected from the maze test. Then, the best concentrations of these eight stimuli and their combination were investigated by the biting-balls test to compound a formula with the strongest appetite for grass carp. The results of behavioral maze test showed that dimethyl-β-propiothetin (DMPT), dimethylthetin (DMT), glycine, taurine, l -glutamic, l -alanine, l -proline, and l -arginine have different degrees of usefulness in attracting grass carp. The electro-olfactogram recoding showed that the EOG response of grass carp to the stimuli is a transient biphasic potential change and all of the eight stimuli could induce the EOG response of grass carp. The biting-balls test showed that glycine, l -glutamic, and l -arginine at 10 −2 mol/L had significant feeding stimulation and DMT at 10 −1 mol/L had significant feeding stimulation than the other groups. Finally, formula 9 composed of DMT, glycine, l -glutamic acid, and l -arginine has the greatest attraction for grass carp. The results of this study verified the attractive effect of some amino acids and other chemicals on grass carp fishing, and would provide support for the production of specific grass carp attractants.